Investigating the sustainability of the Housing Programme of Cornubia, with regards to Sustainable Human Settlements - Bodhi, Kavish (UNIVERSITY OF WITWATERSRAND FACULTY OF ENGINEERING & THE BUILT ENVIRONMENT, 2016)
After the 1994 elections, housing initiatives, aimed to address the inequalities created within Apartheid, such as racial and socio-economic segregation. This resulted in the 1994 White Paper and 1997 Housing Act which encompassed some aspects of the Reconstruction and Development Programme (RDP). However, housing policy implementation was criticised for many reasons. This resulted in emergence of the Breaking New Ground (BNG) policy which aimed at creating sustainable human settlement, as opposed to just housing provision. In the past few years under BNG, government has adopted several programmes that promote the creation of sustainable development, sustainable human settlements and sustainable housing. In order to address this challenge and create sustainable human settlements, the eThekwini municipality envisioned the Cornubia Integrated Human Settlement Project. This is a partnership between the eThekwini municipality and Tongaat Hulett Development. Cornubia proposes a mixed-use development, with retail, commercial, light industry and residential components. The project is still under development, but phase 1a of the housing programme has been completed. The research draws on aspects and principles of sustainable development, sustainable housing and sustainable human settlements; and how the South African government engages with these principles through policies and strategies. Though the state has taken the initiative to provide housing in Durban through the Cornubia development, it is no longer sufficient to just provide housing to people, as a housing development needs to address more issues than accessing shelter. Therefore this research report looks at the sustainability practices and initiatives used within Cornubia’s Housing Programme. There are many plans and strategies put in place to ensure and promote economic, social and environmental sustainability, however, given that the housing programme is still within its early stages of development, many of these plans have either not fully materialised for have not been put in place due to lack of threshold. This results in the reality of what residents experience which contrasts what is proposed for the development, with regards to sustainability. Residents interviewed stated that they have not benefitted much (if not at all) from any plans and strategies that have supposedly been put in place. Over and above advocating for the full implementation of all plans and strategies put in place to create sustainability within the housing programme, the main recommendation of this research report is to address the title deed contract between residents and the eThekwini Municipality. Residents should be able to edit their house or use their house as collateral in order to improve their lives through creating SMMEs or acquiring loans.
Honours Research Report 2016